1998
DOI: 10.1128/mcb.18.6.3580
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleic Acid Binding Activity of Bleomycin Hydrolase Is Involved in Bleomycin Detoxification

Abstract: Yeast bleomycin hydrolase, Gal6p, is a cysteine peptidase that detoxifies the anticancer drug bleomycin. Gal6p is a dual-function protein capable of both nucleic acid binding and peptide cleavage. We now demonstrate that Gal6p exhibits sequence-independent, high-affinity binding to single-stranded DNA, nicked doublestranded DNA, and RNA. A region of the protein that is involved in binding both RNA and DNA substrates is delineated. Immunolocalization reveals that the Gal6 protein is chiefly cytoplasmic and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Rabbit anti-yeast cyclophilin antibodies were a gift from Kathryn Sykes. Immunopurified anti-Gal6 antibodies have been described (40). Alkaline phosphatase conjugated goat anti-rabbit and goat antimouse IgG (Bio-Rad) were used for detection in chemifluorescent Western blots.…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit anti-yeast cyclophilin antibodies were a gift from Kathryn Sykes. Immunopurified anti-Gal6 antibodies have been described (40). Alkaline phosphatase conjugated goat anti-rabbit and goat antimouse IgG (Bio-Rad) were used for detection in chemifluorescent Western blots.…”
Section: Methodsmentioning
confidence: 99%
“…In yeast, Gal6p has been shown to negatively regulate galactose metabolism and also to hydrolyze bleomycin, which is widely used in cancer chemotherapy. Studies show that DNA-binding mutants of Gal6p fail to protect yeast from bleomycin toxicity (25,26). Recent work has shown that the 19 S component of the 26 S proteasome binds specifically to the GAL1-10 promoter and functions in nucleotide excision repair and transcriptional elongation in yeast (27)(28)(29).…”
mentioning
confidence: 99%
“…Two genes involved in galactose metabolism, IMP2 and GAL6/BLH1, share the ability to protect cells from the glycopeptide bleomycin (BLM) (Enenkel and Wolf, 1993;Masson and Ramotar, 1996;Zheng and Johnston, 1998). The protease bleomycin hydrolase (Gal6p/Blh1p) is believed to prevent cytotoxic effects by degrading bleomycin.…”
Section: Discussionmentioning
confidence: 99%
“…In other strains significant differences between the wild-type strain and the gal6 mutant were observed in survival to short-term treatments with bleomycin (Zheng & Johnston, 1998). We then performed the analysis under similar experimental conditions ( Figure 4C).…”
Section: Effect Of the Imp2 Deletion On The Expression Of Gal6mentioning
confidence: 99%